PEMANFAATAN LIMBAH CANGKANG TELUR SEBAGAI PUPUK MAKRO (Ca) PADA TANAMAN BAWANG MERAH - Fetty Dwi Rahmayanti (Agrisia: Jurnal Ilmu-Ilmu Pertanian, 2020)
One of the urban wastes classified as organic waste and originating from households is eggshell waste. According to data from the Business Competition Supervisory Commission (2010), egg consumption in the Jakarta Capital City region in 2007 was 240,900,000, -. The higher the amount of egg consumption in the DKI Jakarta area will result in higher eggshell waste produced, especially in the area of Cipinang Melayu Village, East Jakarta, which intersects with Kalimalang as the Citarum sub-watershed. One alternative to dealing with urban eggshell waste which is classified as organic waste, especially in Cipinang Melayu Village, which is located in the Kalimalang River, which is part of the Citarum sub-watershed, is to use egg shells as fertilizer for eggshell flour for nutrition for plants.               The types of plants that can be selected in the research plan this time are shallot plants. The role of onion is very significant in society, therefore at this time it can be developed as a plant that has a dual function, namely as a cooking spice and as a medicinal plant. It is in line with the program of the Ministry of Agriculture of the Republic of Indonesia, in order to meet the daily needs of shallots for household consumption and in the context of not optimal utilization of yards in urban agriculture, so one way to cultivate shallots for urban communities is through the cultivation method pot.               The research focused on cultivating shallot plants in pots and utilizing waste chicken egg shells and duck egg shells. The eggshell waste will be processed so that it becomes organic fertilizer, namely eggshell fertilizer as nutrition for shallot plants. During the research process, from planting onions to harvesting, each stage of growth and development will be observed. This research is expected to be used as input in urban agricultural learning, especially learning materials in the fields of Agricultural Science, Natural Sciences and Environment.Keywords: Eggshells, Ca Fertilizer, Egg Waste, Shallot Plants